Bi3+/Mn4+ co‐doped dual‐emission phosphors for potential plant lighting. Issue 9 (26th May 2022) - Wu, Sheng; Liu, Quan; Brik, Mikhail G.; Xiong, Puxian; Wang, Dong; Zhang, Guoxing; Chen, Yan
Abstract: Developing environment‐friendly dual‐emission phosphors of both blue–cyan and deep‐red lights is desirable for the utilized indoor plant lighting research. Notably, the naked 6s and 6p Bi 3+ ions are sensitive to the lattice sites, which emit from Ultraviolet (UV) to red lights in various crystal compounds. Meanwhile, the 2 E → 4 A2g transition of Mn 4+ ions promises its deep‐red light emissions, which satisfies the demand for specific wavelength lights for plants growth. Hence, a Bi 3+ /Mn 4+ co‐doped Sr2 LaGaO5 : Bi 3+, Mn 4+ (SLGO:Bi 3+ :Mn 4+ ) phosphor was finally synthesized. The phase, micromorphology and luminescent properties were systematically evaluated. Upon excitation at 350 nm light, dual emissions of both blue–cyan (470 nm) and deep‐red (718 nm) lights were observed. Besides, due to the pronounced photoluminescence (PL) spectral overlap between Bi 3+ and Mn 4+ ions, a potential energy transfer process from Bi 3+ to Mn 4+ ions was confirmed. The relative PL intensities between Bi 3+ and Mn 4+ ions can be tuned just by adjusting the Mn 4+ ion concentration. Besides, Li + co‐doping has been evidenced to improve the deep‐red emissions (718 nm) of SLGO:0.005Mn 4+ due to charge compensation and rationally designed lattice distortion, together with the improved thermal stability. Finally, the emissions of SLGO:Bi 3+, Mn 4+, Li + phosphor suit properly with the absorption of the four fundamental pigments for plant growth, indicating that the prepared phosphorescent materials may have a prospect in plant light‐emitting diodes lighting. Abstract : Bi 3+ /Mn 4+ co‐doped high‐efficiency dual‐emission phosphors Sr2 LaGaO5 :Bi 3+, Mn 4+ for potential plant lighting LEDs